Occupational Health and Safety Analysis of Mining Companies Using Hazard Identification, Risk Assessment, and Risk Control Methods - Tranggono; Kinanti Resmi Hayati; Mochamad Tutuk Safirin; Albertus Adriyanto Satrio Prakosa; Fitriatus Sholeha (Nusantara Science and Technology Proceedings, 2022)
A mining company is a company engaged in the gold mining industry that implements an open-pit mining system. In carrying out mining operations, not all activities will always run smoothly. Based on incident trend data in mining companies, there are still a large number of incidents that occur in mining operational activities each year which result in property damage, minor injuries to workers, serious injuries to workers, occupational diseases, loss of working days, and losses to workers. company. The causes of work accidents are divided into several causes, namely, basic causes, indirect causes, and direct causes. The mining operations of mining companies are not free from hazards and work risks that can occur at any time in the mining work environment, especially in the work area in the pit main ridge. The main ridge pit work area is the main location for gold mining operations for mining companies which are now actively operating for many mining activities such as drilling, blasting, surveying, loading, and hauling activities where the condition of this work area has a relatively high level of danger and risk, by because it is necessary to analyze Occupational Health and Safety using the HIRARC method or identify potential hazards in the pit main ridge work area, then carry out an existing risk assessment to determine a control plan that is suitable for the conditions in the pit main ridge work area.